Effect of Standardized Grape Powder Consumption on the Gut Microbiome of Healthy Subjects: A Pilot Study - Jieping Yang (MDPI AG, 2021)
Grapes provide a rich source of polyphenols and fibers. This study aimed to evaluate the effect of the daily consumption of 46 g of whole grape powder, providing the equivalent of two servings of California table grapes, on the gut microbiome and cholesterol/bile acid metabolism in healthy adults. This study included a 4-week standardization to a low-polyphenol diet, followed by 4 weeks of 46 g of grape powder consumption while continuing the low-polyphenol diet. Compared to the baseline, 4 weeks of grape powder consumption significantly increased the alpha diversity index of the gut microbiome. There was a trend of increasing Verrucomicrobia (p = 0.052) at the phylum level, and a significant increase in Akkermansia was noted. In addition, there was an increase in Flavonifractor and Lachnospiraceae_UCG-010, but a decrease in Bifidobacterium and Dialister at the genus level. Grape powder consumption significantly decreased the total cholesterol by 6.1% and HDL cholesterol by 7.6%. There was also a trend of decreasing LDL cholesterol by 5.9%, and decreasing total bile acid by 40.9%. Blood triglyceride levels and body composition were not changed by grape powder consumption. In conclusion, grape powder consumption significantly modified the gut microbiome and cholesterol/bile acid metabolism.